Implementasi Sistem Informasi Akuntansi : Penggunaan Zahir Accounting pada CV. Anugerah Jaya Plastindo - Fransisca, Fransisca; Arisman, Anton (Universitas Multi Data Palembang, 2024)
Zahir Software is an accounting system or program that can monitor and assist a company's daily financial activities with the final output being an automatic financial report that can be used at any time. The aim of this research is to provide a design overview of the application of Zahir and to determine the obstacle factors in the application of Zahir at CV. Anugerah Jaya Plastindo. The research method used by the author is qualitative descriptive research. The results of this research show that the application of Zahir makes it easier for directors to check financial reports and employees to be helped in carrying out their work and from a tax perspective, sales and purchase transactions can be accounted for when audited by the KPP. Changes can be made when implementing Zahir on the CV. Anugerah Jaya Plastindo.